2022
DOI: 10.1155/2022/9710376
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen (HLA) System: Genetics and Association with Bacterial and Viral Infections

Abstract: The human leukocyte antigen (HLA) system is one of the most crucial host factors influencing disease progression in bacterial and viral infections. This review provides the basic concepts of the structure and function of HLA molecules in humans. Here, we highlight the main findings on the associations between HLA class I and class II alleles and susceptibility to important infectious diseases such as tuberculosis, leprosy, melioidosis, Staphylococcus aureus infection, human immunodeficiency virus infection, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 123 publications
0
43
0
1
Order By: Relevance
“…Numerous studies have found that genetic variations at the loci encoding HLA genes can be associated to an increased or decreased risk of contracting infectious diseases. Research has uncovered a relationship between HLA alleles or haplotypes in major infectious diseases such as bacterial infections (tuberculosis, leprosy, melioidosis, and Staphylococcus aureus) and viral infections (human immunodeficiency virus (HIV) infection, hepatitis B, and hepatitis C) among several populations [7,10]. It is speculative that various HLA alleles may determine the genetic susceptibility to or possibly protection against COVID-19 and can be The association between COVID-19 disease and HLA-DRB1*15 allele was also observed in Iranian population and indeed the allele frequency of HLA-DRB1*15 was found higher in patients with lymphopenia compared to those cases without lymphopenia.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have found that genetic variations at the loci encoding HLA genes can be associated to an increased or decreased risk of contracting infectious diseases. Research has uncovered a relationship between HLA alleles or haplotypes in major infectious diseases such as bacterial infections (tuberculosis, leprosy, melioidosis, and Staphylococcus aureus) and viral infections (human immunodeficiency virus (HIV) infection, hepatitis B, and hepatitis C) among several populations [7,10]. It is speculative that various HLA alleles may determine the genetic susceptibility to or possibly protection against COVID-19 and can be The association between COVID-19 disease and HLA-DRB1*15 allele was also observed in Iranian population and indeed the allele frequency of HLA-DRB1*15 was found higher in patients with lymphopenia compared to those cases without lymphopenia.…”
Section: Resultsmentioning
confidence: 99%
“…79 This characteristic results in a high phenotypic variability of the complex, highlighting the diversity of responses to various pathologies in different ethnic groups. 80,81 There are several HLA haplotypes, with three genes from HLA class I (HLA-A, HLA-B, and HLA-C) mainly related to peptide presentation and activation of CD8+ T cells, and three other genes from HLA class II (HLA-DP, HLA-DQ, and HLA-DR), which differ from class I, are intrinsically linked to CD4+ T-cell peptide presentation. 82,83 In addition, there is also class III HLA, which has genes encoding proteins in the immune system, such as the complement system and cytokines.…”
Section: Hla: Recognition and Antigenic Presentation In The Immune Re...mentioning
confidence: 99%
“…79 This characteristic results in a high phenotypic variability of the complex, highlighting the diversity of responses to various pathologies in different ethnic groups. 80,81…”
Section: Introductionmentioning
confidence: 99%
“…Human leukocyte antigen (HLA) plays an essential role in immune regulation. The polymorphisms of HLA are significantly related to the susceptibility and severity of many diseases, such as tumors (Sadagopan et al 2022 ), autoimmune diseases (Naito and Okada 2022 ), immunodeficiency diseases (Grifoni et al 2015 ), allergic diseases (Daya et al 2021 ), infectious diseases (Medhasi and Chantratita 2022 ), metabolic diseases (Tekola Ayele et al 2012 ), and so on. Each person has multiple alleles that make up the individual HLA type.…”
Section: Introductionmentioning
confidence: 99%